PREDIKSI RELEVANSI NILAI INFORMASI AKUNTANSI TERHADAP FINANCIAL DISTRESS DIMODERASI CAPITAL INTENSITY PADA PEMERINTAH KABUPATEN DAN KOTA DI PROVINSI SUMATERA - Sunardi Sunardi; Ety Murwaningsari (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2021)
This study aims to predict the value relevance of accounting information to financial distress and the role of capital intensity in moderating the relationship between these variables. The research population of 32 district and city governments in South Sumatra and Lampung Provinces. The data source for local government financial reports for 2016 to 2018 is that the amount of data for 96 years of data tests the ability of financial ratios to predict financial distress. The data analysis method uses SPSS logistic regression, the research findings show that financial independence ratios, long-term solvency ratios and short term solvency ratios can negative predict financial distress, while financial flexibility ratios, operating solvency ratios and services solvency ratios can positive predict financial distress, then Intensity capital can moderate (weaken) financial distress for all independent variables. So the local government financial reports have a high relevance value for decision making for the users so that they can detect financial distress.